Comparison of three feline leukaemia virus (FeLV) point-of-care antigen test kits using blood and saliva. (February 2017) - Westman, Mark E.; Malik, Richard; Hall, Evelyn; Sheehy, Paul A.; Norris, Jacqueline M.
Highlights: SNAP FIV/FeLV Combo produced more false-positive p27 test results than Witness FeLV/FIV and Anigen Rapid FIV/FeLV. p27 testing in parallel reduced, but did not completely eliminate, the occurrence of false-positive p27 results. Progressive FeLV infection was more common in younger cats, while regressive FeLV infection was more common in older cats. False-positive p27 results were more common in older cats. More studies are needed before FeLV testing using saliva can be recommended as a screening tool for large populations of cats. Abstract: Feline leukaemia virus (FeLV) can be a challenging infection to diagnose due to a complex feline host-pathogen relationship and occasionally unreliable test results. This study compared the accuracy of three point-of-care (PoC) FeLV p27 antigen test kits commonly used in Australia and available commercially worldwide (SNAP FIV/FeLV Combo, Witness FeLV/FIV and Anigen Rapid FIV/FeLV), using detection of FeLV provirus by an in-house real-time polymerase chain reaction (qPCR) assay as the diagnostic gold standard. Blood ( n  = 563) and saliva ( n  = 419) specimens were collected from a population of cats determined to include 491 FeLV-uninfected and 72 FeLV-infected individuals (45 progressive infections [p27 and qPCR positive], 27 regressive infections [p27 negative, qPCR positive]). Sensitivity and specificity using whole blood was 63% and 94% for SNAP Combo, 57% and 98% for Witness, and 57% and 98% for Anigen Rapid, respectively. SNAP Combo had a significantly lower specificity using blood compared to the other two kits ( P  = 0.004 compared to Witness, P  = 0.007 compared to Anigen Rapid). False-positive test results occurred with all three kits using blood, and although using any two kits in parallel increased specificity, no combination of kits completely eliminated the occurrence of false-positive results. We therefore recommend FeLV proviral PCR testing for any cat that tests positive with a PoC FeLV antigen kit, as well as for any cat that has been potentially exposed to FeLV but tests negative with a FeLV antigen kit, before final assignment of FeLV status can be made with confidence. For saliva testing, sensitivity and specificity was 54% and 100%, respectively, for all three test kits. The reduced sensitivity of saliva testing compared to blood testing, although not statistically significant, suggests saliva testing with the current generation of PoC FeLV antigen kits is unsuitable for screening large populations of cats, such as in shelters.